Iowa gambling task: Administration effects in older adults - Schneider,Daniela Di Giorgio (2007)
Abstract The Iowa Gambling Task (IGT) assesses decision-making. Objective: The objective of the present study was to investigate whether specific changes in administering the IGT can affect performance of older adults completing the task. Method: Three versions of the IGT were compared regarding the feedback on the amount of money won or lost over the course of the test. The first version (I) consisted of a replication of the original version (Bechara et al., 1994), which utilizes a computerized visual aid (green bar) that increases or decreases according to the gains or the losses. The second version (II), however, involved a non-computerized visual aid (cards) and, in the third version (III) the task did not include any visual aid at all. Ninety-seven older adults, divided into three groups, participated in this study. Group I received computerized cues (n=40), group II, non-computerized cues (n=17) and III was submitted to a version without any cues (n=40). Results: The participants without any cues achieved only a borderline performance, whereas for those with non-computerized cues, twice the number of participants showed attraction to risk in relation to those with aversion. The participants of the computerized version were homogeneously spread across the three performance levels (impaired, borderline and unimpaired). Conclusions: Aspects of the complexity of the decision process as well as of the task used are proposed as possible theoretical explanations for the performance variation exhibited.